Cultivation Of Galah Shrimp Using Aquaponic System As An Effort To Improve The Economy In Drin Mangko Village Woyla District - Mahendra Mahendra; Farah Diana; Citra Dina Febrina; Irhami S; Agusriati Muliyana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this research-based community service program is to apply the research results of the proposing team's research for community empowerment. The application of research results is carried out in the aquaculture program on economic biota in the aquaponic system as an effort to improve the economy in Drin Mangko Village, Woyla District, which is a potential for aquaculture that must be developed. The application system is shrimp cultivation with aquaponic technology. Aquaponic technology is a cultivation technique through environmental engineering that relies on oxygen supply and the use of microorganisms that can directly increase the digestibility value of feed. This community service activity aims to increase farmer income with high shrimp productivity and increase shrimp production. The activity was carried out for 6 months at Drin Mangko Village, Woyla District, West Aceh. The results obtained were a relative growth rate of giant prawns of 3.98%. The outputs produced were in the form of international journals, services, and methods as well as mass media.